Representation and termination analysis for ECA rules based on extended Petri net - Li-chen ZHANG; Xiao-ming WANG; Wen-yang DOU (Tongxin xuebao)
In order to improve the accuracy of the termination an lysis on ECA rules, a novel representation model (EPN, extended Petri net) of ECA rules was built. Based on the EPN, an effective termination decision algorithm was discussed and proposed. By using plenty of information about the rule characteristics in EPN, the proposed termination algorithm could comprehensively analyze the influence on the termination analysis. The theoretical analysis and experimental re-sults show that the proposed algorithm has higher accuracy and lower time complexity.